Coextinction Is Magnifying the Current Extinction Crisis, as Illustrated by the Eriophyoid Mites and Their Host Plants - Ozman-Sullivan, Sebahat K.; Sullivan, Gregory T. (Acarologia-Université Paul Valery, 2023)
Coextinction is a major and growing threat to global biodiversity. One of the affected groups is the eriophyoid mites (Prostigmata: Eriophyoidea) which are highly host plant specific. They have been described from an enormous range of annual and perennial plants from grasses to giant forest trees. It is highly likely that there are huge numbers of undescribed eriophyoid species in the subtropical and tropical regions which harbor an extraordinary wealth of plant diversity. The global total of eriophyoid species is estimated to be at least 250,000 but it could be much higher. However, the continuing destruction and degradation of natural habitat, especially tropical forests, and climate change, together pose extreme, on-going threats to the eriophyoid mites because of their vulnerability to co-extinction with their host plants. It has been reported that one third of all the Earth's plant species are now at risk of extinction. Together with enormous numbers of other invertebrate species, it is highly likely that many thousands of eriophyoid species are disappearing in the current mass extinction event. Population decline and co-extinction, especially of the invertebrates, are greatly accelerating total biodiversity losses. The termination of habitat destruction and degradation; establishment of large, representative protected areas; restoration of degraded areas; and rapid reduction of fossil fuel use, are urgent tasks. However, the long term conservation of biodiversity can only be achieved through comprehensive social, economic and political reforms across the world that prioritize environmental protection, peaceful coexistence, social justice and the sustainable use of resources.
Sullivan, Sebahat/0000-0001-5240-8110
Keywords: Biodiversity Conservation; Host Specificity; Symbiosis; Ecological Collapse; Ecocentrism